Conflict in Cities and the Struggle for Modernity. Toward an Understanding of the Spatiality of the October Crisis - Burke, Jason (Cahiers de géographie du Québec, 2009)
AbstractBy the 1960s, Quebec was poised for change. Two visions of a modern Quebec began to emerge that clashed throughout the decade, culminating in what has become known as Canada’s most significant encounter with terrorism: the October Crisis. While the newly elected Liberal government pushed forward with social and economic reforms, the Front de Libération du Québec (FLQ) emerged with a different vision for Quebec characterized by independence and socialism. This article argues that with modernization comes geographical transformation and violence. It looks at the spatial implications of FLQ violence during the 1960s and the government’s response to the October Crisis as an attempt to provide a new understanding of the crisis.